The paradox of safety - challenging the current paradigms of organisation and leadership in the prevention of disasters from high hazard technology. - Cowley, Charles (Cranfield University, 2020)
This qualitative empirical research project has examined the interplay between rule-following and adaptive practice in the safe operation of high hazard technology (‘process safety’) and especially the influence of leadership on the entanglement of these paradoxically different approaches, at three different operational oil & gas and petrochemical sites in the Middle East, Asia-Pacific and Europe. Interviews were conducted with 73 people directly involved in plant operations at these sites, firstly using Repertory Grid technique (Kelly, 1955) to elicit individuals' understanding of process safety through the lens of the unfolding of incidents. A second study used semi-structured interviews to focus on leadership and organization relating to process safety through the lens of Complexity Leadership Theory and Leadership- As-Practice. In a third study a critical review of accident analysis was conducted including the analysis of 194 documents relating to 117 process safety incidents, which was compared with that from the two interview-based studies, and also performed a pilot QCA (Ragin, 1987) to explore the application of this method to analysing process safety accidents. The repertory grid data showed that respondents regard both adaptive and administrative practices as important; however the interview data and analysis of incident investigation reports reflect a narrower range of factors, indicating an institutionalised predisposition towards administrative practices, which can be at odds with respondents’ theory-in- use. There are practical implications for incident investigation processes, which may be overlooking the importance of adaptive practices, for individuals at the sharp end who may be coping with the gulf between what they believe is important and what they bring to the surface, share and document, and for managers who may be constraining the establishment of a climate of psychological safety; all of which may be inhibiting organizational learning that could improve process safety. The research contributes empirical findings that support theories of HRO, System Safety and ‘Safety II’ and support and extend theories of Leadership-As-Practice and Complexity Leadership Theory, and makes recommendations both for research and for management practice.
Keywords: Complexity; entanglement; HRO; leadership practice; organizational learning; process safety; psychological safety; QCA; repertory grid